The impact of sphingomyelin and cholesterol on ordered lipid domain formation in the bovine milk fat globule membrane using artificial giant unilamellar vesicles as a model - Haotian Zheng; Rafael Jiménez-Flores; David W. Everett (JDS Communications)
Giant unilamellar vesicle (GUV) bilayers were constructed from polar lipids and cholesterol by electroformation as a model system to investigate the formation of ordered lipid domains (OLD) within the milk fat globule membrane (MFGM). Dark regions without fluorescent staining on the surfaces of GUV, observed by confocal laser scanning microscopy, were characterized as OLD. Lipid formulations were designed by mixing 1,2-dipalmitoyl-sn-glycero-3-phosphocholine; 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine; milk sphingomyelin; and cholesterol with designated molar ratios to reveal the key components responsible for segregated OLD formation. Cholesterol, rather than milk sphingomyelin, was more responsible for OLD formation. Dark regions were observed in GUV, which contained sphingomyelin but no cholesterol. This observation revealed that at room temperature (below the melting transition temperature [Tm]), not only do cholesterol-mediated ordered domains contribute to lipid phase separation, but phospholipids with high Tm in MFGM are also segregated from the bright fluorescent liquid-disordered domains. This work provides visible evidence demonstrating the comparative roles of sphingomyelin and cholesterol in forming OLD in phospholipid bilayers.